Kinerja Perusahaan Perbankan Syariah Di Indonesia: Pembiayaan Murabahah, Musyarakah, Ijarah - Noor, Muhammad; Anugrah, M. Sahib Saesar; Firmansyah, Amrie (Jurnal Ilmiah Manajemen Kesatuan, 2020)
Firm value is a reflection of market performance. Furthermore, firms can be observed by their operational performance. One of the essential aspects of operating performance is profitability. This study aims to analyze Murabahah, Musyarakah, and Ijarah on the firm performance on Sharia Bank. The firm performance consists of both operation performance, which is represented by profitability, and market performance, represented by firm value. This research employs the quantitative method. This research used secondary data from sharia bank monthly reports from 2018 to 2020 obtained from IDX. Using purposive sampling, the selected samples in this research has 84 observation. The hypothesis examination used in this research is multiple linear regression analysis of pooled data. This study finds that murabahah has a positive effect on profitability, musyarakah has a negative effect on profitability, ijarah does not affect profitability, murabahah, and musyarakah does not affect firm value. In contrast, ijarah has a negative effect on firm value. Keywords: Murabahah, Musyarakah, Ijarah, Firm Performace.